Sexual dimorphism in elite volleyball players - Sterkowicz, S.; Zak, S. (Journal of Kinesiology and Exercise Sciences, 2010)
Aim of the study. (1) Determination of the level of physical development in elite male and female volleyball players. (2) Assessment of motor effects achieved during volleyball-specific tests. (3) Investigations of sexual dimorphism for the characteristics of body build and motor abilities among persons who play volleyball. Material and method. In the group of 144 female and 144 male players, the participants of the Olympic volleyball tournament (Beijing 2008), age, body height, mass, body mass index and special physical fitness (which covered maximal arm reach in attach and defence) were determined and analysed with regard to sexual dimorphism. After that, sexual dimorphism index (SDI) was calculated. Interpretation of the results took into consideration the factor of tactical formation at five levels: opposite, libero, outside hitter, setter and middle blocker. Results. The highest level of sexual dimorphism (independent of tactical formation) was confirmed for BMI variable. Considerably higher level of sexual differences in arm reach (attack and defence) than in body size in favour of men was also noticed. All observed differences were determined in relation to net`s height over which male and female volleyball players play. Conclusions. All these who play volleyball are distinguished by a huge body height. Compared with Ross standard, body mass for players in each tactical position is lower. Opposites diverge from this standard the most, whereas middle blockers are best fitted. Somatic and motor demands of the game at different tactical positions should be taken into consideration during selection and volleyball training. Considerably higher dimorphism in the area of energy abilities rather than somatic abilities should postulate the increase in net`s height for the men. Solving this problem through other modifications of volleyball rules is also taken into account.